Revisiting the taxonomy and nomenclature of Eriocaulon modestum (Eriocaulaceae) - Chagas, Earl Celestino De Oliveira; Costa-Lima, James Lucas Da (Phytotaxa, 2020)
The taxonomy of Eriocaulon modestum and its infraspecific taxa is revised. Eriocaulon modestum var. brevifolium and E. modestum f. viviparum are accepted as distinct taxa and raised to the species level under the names E. candango E.C.O.Chagas and E. ibeji E.C.O.Chagas, respectively. We present a complete list of synonyms and examined specimens of E. modestum and a comparative morphological table for the three species. In addition, we designate lectotypes for the names E. modestum and its synonyms E. burchellii, E. glaziovii, E. melanolepis, and E. proximum.